Design of Portable Hand Winch Tool for Stack Emission Monitoring Works - Maccolin, Ian Bidick; Hassan, Mohd Fahrul (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Winch is a mechanical apparatus utilized for either winding up or unwinding a rope or wire cable, which is connected to a load through a horizontally rotating drum. The fundamental structure of a winch typically includes a spool for coiling the rope and a hand crank for operating the spool. In traditional practice, winches were operated manually, relying on human labor. However, in modern times, winches are commonly powered by motors or hydraulics, as they provide substantial torque necessary for tasks involving heavy loads. Nonetheless, manual winches still exist and are suitable for lighter load applications. During stack monitoring operations, industrial emission platforms like those found on boilers typically have a high height to perform related tasks, technicians must climb up these platforms using ladders and carry essential tools, often including a 90m rope. When there is a need for heavy lifting, such as installing new dust or smoke sensors, technicians usually rely on the rope to pull the equipment up. This process demands a considerable amount of energy and can quickly exhaust the technicians. By designing a suitable tool for this purpose, it is possible to enhance both the quality and safety of the working procedures. To design the machine, this project follows the George E. Dieter design process, which entails eight stages: problem definition, information gathering, concept generation, concept evaluation, product architecture, configuration design, parametric design, and detail design. The current patent and commercially available machines were consulted to come up with ideas and concepts for the machine. The generated idea and concept will next be modelled using the SolidWorks program. For this machine, engineering simulation and sustainability analysis are also being done using SolidWorks software. The results based on SolidWorks simulation shows that the designed tool is capable of handling required load reliably and safely where the factor of safety (FOS) for casing and drum are 5.5 and 4.6 respectively. The project's goal was also accomplished because, in theory, the machine can carry out and function properly for stack emission monitoring works application.